Optimization of the parameters for obtaining zirconiaalumina coatings, made by flame spraying from results of numerical simulation (2017)
The K-Sommerfeld values (K) and the melting percentage (% F) obtained by numerical simulation using the Jets et Poudres software were used to find the projection parameters of zirconia-alumina coatings by thermal spraying flame, in order to obtain coatings with good morphological and structural properties to be used as thermal insulation. The experimental results show the relationship between the Sommerfeld parameter and the porosity of the zirconia-alumina coatings. It is found that the lowest porosity is obtained when the K-Sommerfeld value is close to 45 with an oxidant flame, on the contrary, when superoxidant flames are used K values are close 52, which improve wear resistance.